The Role of Education in the Church to Equip Generation Z in Maintaining the Faith for the Implementation of the Great Mandate - Damanik, Roy; Yuli, Purwisasi (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2023)
Generation Z lives in a digital age, which is selfish and forgets the great task that God has given to believers. The Church is responsible and has an important role to play in preparing Generation Z for the implementation of this great mandate. The purpose of this research is to find out the needs of youth in carrying out the great mandate. This article was written using qualitative research methods with a literature study approach, by describing the concept of theological studies of the role of the church in equipping Generation Z in defending the faith for the implementation of the great mandate. it was found that teenagers in this era need the role of the church to form them into disciples who can make disciples, the church must equip Generation Z to carry out Jesus' commands to non-believers.